2021
DOI: 10.1101/2021.09.16.21263698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mortality in Rural Coastal Kenya measured using the Kilifi Health and Demographic Surveillance System: A 16-year descriptive analysis

Abstract: Background The Kilifi Health and Demographic Surveillance System (KHDSS) was established in 2000 to define the incidence and prevalence of local diseases and evaluate the impact of community-based interventions. KHDSS morbidity data have been reported comprehensively but mortality has not been described. This analysis describes mortality in the KHDSS over 16 years. Methods We calculated mortality rates from 2003-2018 in four intervals of equal duration and assessed differences in mortality across these inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…This design was however suitable at the time of the pandemic and further corresponded to WHO recommendations. 53 Estimating excess mortality requires an estimate of a certain level of baseline mortality to enable computation of excess mortality. Quanti cation of burial sites using geospatial analysis is a new method that emerged during the pandemic and was found to have considerable advantages for rapidly monitoring population mortality in settings without effective vital registrations.…”
Section: Discussion Of Key Ndingsmentioning
confidence: 99%
“…This design was however suitable at the time of the pandemic and further corresponded to WHO recommendations. 53 Estimating excess mortality requires an estimate of a certain level of baseline mortality to enable computation of excess mortality. Quanti cation of burial sites using geospatial analysis is a new method that emerged during the pandemic and was found to have considerable advantages for rapidly monitoring population mortality in settings without effective vital registrations.…”
Section: Discussion Of Key Ndingsmentioning
confidence: 99%
“…MATLAB program reported a decrease in maternal and under 5 years mortality from 412 to 131 per 100,000 pregnancies and 59.1 to 43.5 per 1000 live births respectively [7]. The Kilifi Health and Demographic Surveillance System (KHDSS) was established in 2000 by the KEMRI-Wellcome Trust Research Program (KWTRP) which reported a reduction in under-5 mortality from 13.1 to 7.4 deaths per 1000 person-years of observation (PYO) from 2013 to 2015, with a further decline of 5.4 deaths per 1000 PYO from 2015 to 2018 [8]. These programs not only showed improvement in health outcomes but also yielded critical insights for guidelines and best practices for community-based MNCH programs [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Although, the indicators for success of CHWs in LMICs are well established (7,8), the perceptions of the communities towards them is relatively understudied. According to a study conducted in Kenya, CHWs were perceived by the community as facilitators for care seeking and health education in the community [10].…”
Section: Introductionmentioning
confidence: 99%